Views on clinically suspect arthralgia: a focus group study. Issue 5 (May 2016) - Newsum, Elize; van der Helm-van Mil, Annette; Kaptein, Adrian
Abstract The rheumatology field is moving towards identifying individuals with an increased risk for rheumatoid arthritis (RA) at a stage when arthritis is still absent but persons having clinically suspect arthralgia (CSA). Incorporating patients' views in rheumatologic care is pivotal; however, the views of persons with CSA on their condition are unknown. We aimed to help fill this gap by exploring illness perceptions of persons with CSA and their views on hypothetical prognoses for developing RA. Persons with CSA were invited to participate in a semi-structured focus group discussion. Illness perceptions according to the Common Sense Model (CSM) and four a priori formulated themes were explored in detail during the group discussion. The discussion was audio-taped and transcribed verbatim. Transcripts were analysed in an interpretative phenomenological approach manner, on the basis of the dimensions of the CSM by three researchers independently. The views of four participants with CSA were explored during one focus group discussion. Four dimensions of the CSM were mainly observed: Identity, Consequences, Personal Control and Concern. None of the patients identified themselves as being a patient. They did experience pain and impairments in daily functioning and were concerned that their symptoms would progress. In the absence of physician-initiated treatment, some patients changed lifestyle in order to reduce pain and to promote health. Patients unanimously said that they could not interpret prognostic information on RA development expressed in hypothetical chances. Persons with CSA do not consider themselves patients. Prognostic information related to the development of RA based on risk percentages was considered as not useful by persons with CSA. Understanding of the illness perceptions of persons with CSA by health care professionals might improve medical management and facilitate shared decision-making.